Importance of natural dust in controlling the acidity of rain over India (MAUSAM, 1986)
pH data of rainwater samples and of soils from India have been studied to assess the importance of natural dust in controlling the acidity of rain. It has been found that pH of rainwater is influenced to a large extent on the pH of soil and the dust load in the surrounding region. Indian soils are normally basic Srivastava in character (pH in basic range) and the dust load is quite high, as such, pH values of rain are in general in basic and help' range. Further, the effect of acid rain over India (on lakes and soil), in general, may not be pronounced due to high values of cation exchange capacity of soils and pH of surface water.